2007
DOI: 10.1093/jac/dkm406
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines for antibiotic prophylaxis in general surgery: a critical appraisal

Abstract: Adherence to separate aspects of guidelines for surgical prophylaxis has to be improved. The duration of antibiotic prophylaxis was the main parameter of interest. Interventions have to be made about the development, distribution and adoption of adequate guidelines in collaboration with surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
114
16
21

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(160 citation statements)
references
References 16 publications
9
114
16
21
Order By: Relevance
“…However, this result is close to those found by other authors, whose rates varied between 81% and 88.1% 16,17,20,27 . .…”
Section: Assessment Of Antibiotic Prophylaxis In Surgical Patients Atsupporting
confidence: 92%
See 3 more Smart Citations
“…However, this result is close to those found by other authors, whose rates varied between 81% and 88.1% 16,17,20,27 . .…”
Section: Assessment Of Antibiotic Prophylaxis In Surgical Patients Atsupporting
confidence: 92%
“…, Tourmousoglou et al 16 , Pitallis et al 15 and Hohmann et al 25 showed contrasting results with the present study, the values being 5.8%, 20%, We must note the current trend of antibiotic prophylaxis restricted to surgical time 9 .…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…Several studies assessing compliance with surgical prophylaxis guidelines in hospitals abroad have been published [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Overall compliance to guidelines has varied from as low as 0-53%, usually in the range of 20-30%.…”
Section: Discussionmentioning
confidence: 99%